Needle ZrO x loaded NiFe2O4 catalysts for Photo-Fenton degradation of bisphenol A and 4 nitrophenol - Velu Manikandan; Duraisamy Elango; Velu Subash; Ponnuchamy Kumar; Jeyakumar Saranya Packialakshmi; Palaniyappan Jayanthi; You Jae Sun; Kwang Soup Song (npj Clean Water)
Abstract This study investigates the synthesis of ZrO x -loaded NiFe2O4 photocatalysts (1, 2, and 3 wt%) through co-precipitation and wet impregnation methods for environmental and health applications. The structural analysis revealed a cubic crystal structure, with ZrO x doping enhancing charge separation and mobility by converting the morphology from fibrous to needle-like. Under visible light (VL) and H2O2 activation, the ZrO x (3 wt%)/NiFe2O4 composite achieved high degradation efficiencies (98.5% for Bisphenol A and 98.2% for 4-Nitrophenol) in 120 min via the Photo-Fenton mechanism. Kinetic analysis showed pseudo-first-order behavior with rate constants of 0.945 min−1 for BPA and 0.904 min−1 for 4-NP. The catalyst demonstrated stability with 91.5% efficiency retention after multiple cycles. DFT calculations indicated favorable HOMO-LUMO alignments and electrostatic potentials. Additionally, ZrO x (3 wt%)/NiFe2O4 exhibited selective cytotoxicity against breast cancer cell lines, while maintaining high viability in HEK-293 cells. The results suggest that ZrO x (3 wt%)/NiFe2O4 composites are promising for environmental and biomedical applications.